Stories of Afghanistan Beyond the War:: Visual Mobile Communication Via @everydayafg on Instagram - Veloso da Silva, Admilson; Muratalieva , Aizhamal (Filológia.hu, 2024)
Afghanistan has been depicted in traditional Western media as a violent place due to wars and conflicts, but visual mobile social media, such as Instagram, may contribute to changing its depiction by diversifying the content and narratives. Hence, this paper analyses how Afghanistan is presented by collective photographers on @everydayafg, based on three aspects: what/who is visually depicted, what actions/issues are discussed, and what associations are made in the posts. Applying netnography and content analysis, we systematically sampled and coded the first monthly photo since the account creation (2014/2021, N = 76). Results demonstrate that @everydayafg deviates from representations of violence in at least three ways: 1) depicting Afghanistan with human agents; 2) covering more favourable and uplifting topics, as for tourist destinations; and 3) associating the country with a “place of living” and with its “cultural richness”. However, some narratives still raise significant issues, such as human rights and labour conditions in the region. Hence, Instagram is used to challenge prevalent perspectives in the media while generating awareness of relevant local problems.